Wealth comparison across social distances: implications for well-being - Wu, Yingying; Tang, Qinglan; Huang, Zhongli; Liu, Ziyu; Liang, Kayan (Frontiers in Psychology, 2025)
IntroductionIn today’s digitally connected and economically unequal world, upward wealth comparisons are pervasive. This study examined how wealth comparisons across different social distances (family, friends, and internet) distinctly affect well-being.MethodsWe employed a scenario-based questionnaire design to assess the effects of wealth comparisons. Data were analyzed using regression models, with stress tested as a mediator through mediation analysis and heterogeneous effects explored across subgroups based on help-seeking behaviors.ResultsComparisons with all three groups are associated with negative influence on well-being, with comparisons to friends exhibiting the strongest effect. Stress mediates these impacts, while help-seeking behaviors show divergent pathways. Additionally, life satisfaction and income buffer sensitivity to disparities.DiscussionThe findings underscore that the risk of upward wealth comparisons is contingent on social distance. This research integrates offline and online dynamics into a cohesive theoretical framework, advancing social comparison theory and providing actionable insights for interventions designed to protect well-being in the face of pervasive social comparison.